THE AESTHETICAL LITERACY IN THE CONSOLIDATION OF READING AND WRITING OF YOUNG AND ADULT PEASANTS - Araujo, Gustavo Cunha de; Miguel, Jose Carlos [UNESP]; Silva, Edimila Matos da (Univ Estadual Sudoeste Bahia, 2019)
The main objective of this research is to investigate how aesthetic literacy is developed from visual signs and writing to understand the reality of Brazilian youth and adult rural education. This study was based on Historical-Cultural theory and had as a method the Didactic-Formative Experiment. Correcting or alleviating problems that appear in reading and writing, seeking to improve them is a way of thinking about a possibility of multi literacy, in which the aesthetic literacy configures an essential aspect, because in the research, the students started to write better after producing comics books. They improved their writing. This is beautiful, beauty: character of well-done; coherent, defined, with good form.
Keywords: Aesthetic Literacy; Arts; Rural Education; Theoretical Thought; Young and Adults Education